The effect ofskeletal Class Ⅲ high angle with deviation on upper airway morphology and hyoid position - WANG Gang, TANG Jinqiao, FENG Yu, LI Mengru, WANG Xiaoqin (Editorial Office of Stomatology, 2024)
Objective To apply cone beam CT measurements(CBCT)to analyze the effect of skeletal Class Ⅲ high angle with deviation on upper airway morphology and hyoid position. Methods A total of 120 patients with skeletal Class Ⅲ high angle malocclusion who visited our hospital from September 2019 to December 2022 were selected. CBCT was taken in all subjects. According to the degree of mandibular deviation (MD) of the point under the chin from the median sagittal plane, the 120 patients were divided into three groups: non-migratory, mildly migratory, and severely migratory groups, and the volume of the upper airway as well as the position of the hyoid bone of three groups were measured and analyzed respectively. Results There was no significant difference in the volume and minimum cross-sectional area of the nasopharyngeal segment, palatopharyngeal segment, and minimum cross-sectional area of the laryngopharyngeal segment. No siginificant difference was found between the position of the hyoid bone(HB) on the Y-axis (Y-HB) and the position of the hyoid bone on the Z-axis(Z-HB) among the three groups(P>0.05). Compared with the other two groups, the volume and total volume of the nasopharyngeal segment, the laryngopharyngeal segment, and minimum cross-sectional area of the laryngopharyngeal segment in the group of severe deviation were significantly reduced(P<0.05) and X-HB was significantly larger(P<0.05). Conclusion In patients with skeletal Class Ⅲ hyperkeratosis with severe deviation, the total volume of the glossopharyngeal segment, laryngopharyngeal segment, and upper airway, as well as the minimum cross-sectional area of the glossopharyngeal segment were smaller than those of the othertwo groups. In patients with severe deviation, the position of the hyoid bone(HB) in the X-axis(X-HB) was larger than that of the non-migratory group, indicating that migratory jaws mainly affect the morphology of the lingual-pharyngeal segment as well as the laryngopharyngeal segment of the upper airway;the effect of migratory jaws on the hyoid bone is reflected in the X-HB, indicating that migratory jaws can lead to the deviation of the hyoid bone from the median sagittal plane.